A presynaptic congenital myasthenic syndrome attributed to a homozygous sequence variant in LAMA5. Issue 1 (28th January 2018) - Maselli, Ricardo A.; Arredondo, Juan; Vázquez, Jessica; Chong, Jessica X.; Bamshad, Michael J.; Nickerson, Deborah A.; Lara, Marian; Ng, Fiona; Lo, Victoria Lee; Pytel, Peter; McDonald, Craig M.
Abstract: We report a severe defect of neuromuscular transmission in a consanguineous patient with a homozygous variant in the laminin α5 subunit gene ( LAMA5 ). The variant c.8046C > T (p.Arg2659Trp) is rare and has a predicted deleterious effect. The affected individual, who also carries a rare homozygous sequence variant in LAMA1, had normal cognitive function, but magnetic resonance brain imaging showed mild volume loss and periventricular T2 prolongation. Repetitive nerve stimulation at 2 Hz showed 50% decrement of compound muscle action potential amplitudes but 250% facilitation immediately after exercise, similar to that seen in Lambert–Eaton myasthenic syndrome. Endplate studies demonstrated a profound reduction of the endplate potential quantal content but normal amplitudes of miniature endplate potentials. Electron microscopy showed endplates with increased postsynaptic folding that were denuded or only partially occupied by small nerve terminals. Expression studies revealed that p.Arg2659Trp caused decreased binding of laminin α5 to SV2A and impaired laminin‐521 cell adhesion and cell projection support in primary neuronal cultures. In summary, this report describing severe neuromuscular transmission failure in a patient with a LAMA5 mutation expands the list of phenotypes associated with defects in genes encoding α‐laminins.